(Dis) Connecting with the Ummah in e-Spaces: How Latino Muslims Shape Their Identity Through the Internet?. Issue 2 (2nd April 2020) - Gomez, Diana Carolina Zuniga; Ozkan, Mehmet
Abstract: This article aims to give a better understanding of the role and dynamics of communities in Latino Muslims' online lives. Latinos extensively use online spaces as a way of learning, connecting and interacting. This is not an exception for Latino Muslims. This study answers the question of how and in what form the online presence of Muslims in Latin America creates a sense of belonging as part of the Ummah ; and in what way their interests are converged with those of Muslims in other parts of the world. Focusing on structure and practices, authority and hierarchy, and the broader connections with other (e-) communities, this paper argues that Latino Muslims are highly disconnected from the overall Muslim world and there should be an initiative to connect them with the Muslim world based on their needs, conceptions and perspectives.